FAKTOR-FAKTOR PENGGUNAAN OUT-OF-POCKET PADA PESERTA BPJS PBI DI KLINIK “ASIH SASAMA” - Azizah Boenjamin; Diah Ayu Puspandari (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2022)
Background: The Social Security Administering Body (Badan Penyelenggara Jaminan Sosial, BPJS) established a health system based on Social Health Insurance called the National Health Insurance (Jaminan Kesehatan Nasional, JKN). The current implementation still does not meet one of the Universal Health Coverage (UHC) indicators, namely protection against financial risks due to the high use of Out-of Pocket (OOP). Many JKN participants still choose to seek treatment at the Primary Healthcare (FKTP) they are not registered in, resultingin OOP use.Objective: This study aims to explore the factors that cause the use of OOP in BPJS subsidized scheme participants who seek treatment in Outpatient Primary Clinic